Optimisation des paramètres de fonctionnement de la colonne du Débutaniseur du complexe de traitement du gaz naturel SH-FCP - Hicham, ATOUSSI; Abdelbasset, RAMDANI (University of El-Oued, 2020)
"The world consumption of LPG is in continuous growth, due to its balance sheet and reliable economic as a clean and efficient fuel for the future, it is highly recommended to produce it respecting standards and specifications well determined. The objective of this work is to study the influence of the changing steam composition which is feeding the separation unit over production norms of LPG and Gasoline, for this reason, we chose the gas processing unit of MLE as example of work. We had used the simulator Aspentech HYSYS to evaluate the current case and optimize the parameters of fractionation columns in order to get the final products respecting the standards and specifications required. " "إن الاستهلاك العالمي لمادة غاز البترول المميع في ازدياد مستمر، باعتبار حصيلته الاقتصادية مربحة وبأنه وقود نظيف وفعال للغد، لذا فإن إنتاج هذا الأخير يخضع لمقاييس وخصائص محددة بدقة. إن الهدف من هذا العمل هو دراسة تأثير تغير طبيعة الشحنة البترولية التي تغذي وحدة الفصل على نقاوة ومعايير إنتاج غاز البترول المميع و البنزين ولهذا الغرض قمنا باختيار وحدة معالجة الغاز لحقل منزل لجمات الشرق كمثال عملي. لقد قمنا بإستخدام برنامج المحاكاة أسبنتاك هايسيس لتقييم حالة وحدة الغاز حاليا والقيام بمفاضلة العوامل على أعمدة الفصل للحصول على منتجات نهائية تخضع للمقاييس والخصائص المطلوبة. "
Génie Pétrochimie مذكرة ماستر تخصص
Keywords: Simulation, optimization, LPG, Gasoline, Aspentech HYSYS; المحاكاة، الأمثلية، غاز البترول المميع، البنزين، أسبن تك هايسيس